Seller Protection in Executed Indonesian Land Sale Deeds: Legal Consequences of Buyer Default - Johannes Mangapul Turnip (LPPM Universitas Harapan Bangsa, 2026)
This study analyzes legal protection for sellers in land sale transactions that have been formalized in a Sale and Purchase Deed when the buyer commits default by failing to pay the agreed purchase price. The principal issue centers on the tension between the function of the Sale and Purchase Deed as an authentic instrument possessing full evidentiary force and as the administrative basis for the registration of the transfer of rights, and the reality of non-fulfillment of payment as the buyer’s primary obligation. The research employs normative legal methodology using statutory and case approaches through the examination of land law and contract law provisions as well as judicial reasoning in relevant court decisions. Primary, secondary, and tertiary legal materials are analyzed qualitatively through systematic and teleological interpretation in order to construct coherent juridical arguments. The findings indicate that buyer default does not automatically invalidate the Sale and Purchase Deed, but it may serve as a basis for annulment or legal restoration through a final and binding court decision. The Sale and Purchase Deed retains its formal evidentiary strength; however, its legal consequences may be contested where the declaration of full payment is not supported by valid and sufficient proof of payment. This study emphasizes the necessity of integrated seller protection through preventive and repressive mechanisms, as well as a substantive interpretation of the contemporaneous payment principle to ensure that formal compliance does not conceal material injustice.